Evaluation of Wheeling Charge in Context of Nepalese Power Market - Bhattarai, Prajwal; Adhikari, Yubaraj; Neupane, Sanjaya (Journal of Advanced College of Engineering and Management, 2024)
In case of power system operating under deregulated environment, there will be a transmission company whose major task is to construct, own and operate the transmission system. On evacuating the powers, it charges wheeling charge to the user. However, it should be ensured that the wheeling charges paid by the user must be fair and accurate. The wheeling charge in context of Nepalese power market is evaluated considering the transmission line of three different voltage levels 132 kV, 220 kV, and 400 kV. Annual operation and maintenance cost of 1% of capital cost is also considered to evaluate the wheeling charge. In order to charge the user fairly, wheeling charge in context of Nepalese power market considering the Integrated Nepal Power System of year 2040 is evaluated (i) without considering transmission losses (ii) considering the transmission losses (iii) considering power factor of 0.8 and (iv) considering the power factor of 0.9 for reference power factor of 0.85.